Analisis Komunikasi Asosiatif dan Disosiatif Anatara Seventeen dan Carat Di Weverse - Kinanti, Azzahra Woro; Fadillah, Dani (Borobudur Communication Review, 2026)
This research examines the associative and dissociative communication between the group SEVENTEEN and its fans, Carat, on the Weverse platform. Apps like Weverse have made the relationship between idols and fans increasingly dynamic in the digital age, enabling two-way communication through posts, comments, and live streams. However, this communication pattern often blends positive support with potential conflict—an issue that has not been widely discussed within the Indonesian fandom. The research question focuses on how associative communication (support, solidarity) and dissociative communication (reprimands, privacy boundaries) emerge in interactions and how this impacts the cohesion of the digital community. For observations conducted from December 2024 to June 2025, a qualitative method employing virtual ethnography and content analysis was applied. This utilized data triangulation from screenshots and field notes. The results reveal distinct patterns: associative communication through support (such as Dino’s “chanranghae”) and humor (such as Vernon-Carats), and dissociative communication through subtle reprimands (such as S. Coups and Woozi addressing inappropriate jokes). The negotiation of symbolic meaning reinforces loyalty and norms, according to symbolic interaction theory. On Weverse, communication fosters healthy fandom dynamics through a balance of associative (strengthening emotional bonds) and dissociative (maintaining ethical boundaries) interactions. This contributes to studies of digital communication and entertainment industry strategies.